GENOTYPIC VARIATION IN POLLEN BIOLOGY OF J TION IN POLLEN BIOLOGY OF JACKFRUIT (Artocarpus heterophyllus Artocarpus heterophyllus Artocarpus heterophyllus lam .) - ADITI GUHA CHOUDHURY; S. K. SARKAR; B. C. DAS, SONAM ONGMU BHUTIA (The Bioscan, 2018)
A study on pollen biology of jackfruit was carried out among ten genotypes, selected from germplasm block of AICRP on fruits, Bidhan Chandra Krishi Viswavidyalaya, Mondouri, Nadia, West Bengal. The study revealed that the pollen diameter varied from 15.50µ to 19.42µ with Genotype No. 10/4 having the maximum value. On staining of pollen grains with 1% acetocarmine exhibited maximum pollen viability (96%) in Genotype No. 10/ 10. Pollen germination was observed with variable concentration of sucrose solution i.e. 10%, 15%, 20% and 25% along with 1% agar where 25% sucrose showed no germination at all. Germination with respect to genotypes and media was maximum (78.79%) in Genotype No. 10/10 along with 10% sucrose + 1% agar & 6 hours after pollen planting. The mean data regarding pollen germination & pollen tube growth were highest in 10% sucrose + 1% agar media i.e. 71.75% and 35.40µm respectively irrespective of genotype. So the above study leads to a precise conclusion that 10% sucrose+1% agar act as best in vitro germination medium for jackfruit pollens and all genotypes exhibited high pollen fertility with Genotype No. 9/8, 11/10 and 10/4 will play important role as superior male parents with high number of fertile pollens.